Role of contraction duration in inducing fast‐to‐slow contractile and metabolic protein and functional changes in engineered muscle. Issue 10 (October 2015) - Khodabukus, Alastair; Baehr, Leslie M.; Bodine, Sue C.; Baar, Keith
<x xml:space="preserve">Abstract</x> The role of factors such as frequency, contraction duration and active time in the adaptation to chronic low‐frequency electrical stimulation (CLFS) is widely disputed. In this study we explore the ability of contraction duration (0.6, 6, 60, and 600 sec) to induce a fast‐to‐slow shift in engineered muscle while using a stimulation frequency of 10 Hz and keeping active time constant at 60%. We found that all contraction durations induced similar slowing of time‐to‐peak tension. Despite similar increases in total myosin heavy (MHC) levels with stimulation, increasing contraction duration resulted in progressive decreases in total fast myosin. With contraction durations of 60 and 600 sec, MHC IIx levels decreased and MHC IIa levels increased. All contraction durations resulted in fast‐to‐slow shifts in TnT and TnC but increased both fast and slow TnI levels. Half‐relaxation slowed to a greater extent with contraction durations of 60 and 600 sec despite similar changes in the calcium sequestering proteins calsequestrin and parvalbumin and the calcium uptake protein SERCA. All CLFS groups resulted in greater fatigue resistance than control. Similar increases in GLUT4, mitochondrial enzymes (SDH and ATPsynthase), the fatty acid transporter CPT‐1, and the metabolic regulators PGC‐1α and MEF2 were found with all contraction durations. However, the mitochondrial enzymes cytochrome C and citrate synthase were increased to greater levels with contraction durations of 60 and 600 sec. These results demonstrate that contraction duration plays a pivotal role in dictating the level of CLFS‐induced contractile and metabolic adaptations in tissue‐engineered skeletal muscle. J. Cell. Physiol. 230: 2489–2497, 2015. © 2015 The Authors. Journal of Cellular Physiology Published by Wiley Periodicals, Inc.